1992
DOI: 10.1111/j.1399-3054.1992.tb04674.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of protochlorophyllide and protochlorophyllide esters in roots of dark‐grown plants

Abstract: The protochlorophyll pools of roots of dark‐grown wheat (Triticum aestivum L. cv. Walde), maize (Zea mays L. cv. Goldcrest) and wrinkledseeded pea (Pisum sativum L. ssp. sativurh cv. Kelvedon Wonder) were investigated by high performance liquid chromatography (HPLC) and low temperature fluorescence spectroscopy. All roots contained protochlorophyllide and esterified protochlorophyllides (protochlorophylls) but with considerably larger relative amounts of the latter compared with etiolated leaves. The alcohol m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…When PChl frotn wheat roots was applied to the HPLC-system, four different esterified PChl-forms could be separated showing the same elution profile as described by Me Ewen and Lindsten (1992), Four peaks couid be observed (Fig, 5a) which belong to PChlGG (1), PChlDHGG (2), PChlTHGG (3) and PChlphytol (4) according to these authors. The major part of the PChl was esterified with phytol as was observed previously (Me Ewen and Lindsten (1992), When fractions of the two PChl derivatives from Scenedesmus ohiiquus mutant C-2A' purified by HPLC on polyethylene were analyzed, the elution profiles of MVand DV-PChl also showed four peaks (Fig. 5b,c).…”
Section: Molecular Masses Of Mv-and Dv-pchlsupporting
confidence: 78%
“…When PChl frotn wheat roots was applied to the HPLC-system, four different esterified PChl-forms could be separated showing the same elution profile as described by Me Ewen and Lindsten (1992), Four peaks couid be observed (Fig, 5a) which belong to PChlGG (1), PChlDHGG (2), PChlTHGG (3) and PChlphytol (4) according to these authors. The major part of the PChl was esterified with phytol as was observed previously (Me Ewen and Lindsten (1992), When fractions of the two PChl derivatives from Scenedesmus ohiiquus mutant C-2A' purified by HPLC on polyethylene were analyzed, the elution profiles of MVand DV-PChl also showed four peaks (Fig. 5b,c).…”
Section: Molecular Masses Of Mv-and Dv-pchlsupporting
confidence: 78%
“…This proposal was based on findings that, depending on the plant species investigated and the experimental conditions used, either the 3monovinyl or 3,8-divinyl forms of Pchlide a predominated (Tripathy and Rebeiz, 1988). Later studies, however, showed that esterified forms of only 3-monovinyl but not of 3,8-divinyl Pchlide a could be detected in most plants, with geranylgeraniol, dihydrogeranylgeraniol, tetrahydrogeranylgeraniol, and phytol being the alcohol moieties (McEwen and Lindsten, 1992). Similar to these findings, only the phytol esters of 3-monovinyl Pchlide b could be isolated from diverse plant species (Shedbalkar et al, 1991).…”
Section: Biosynthesis Of Chlorophylls Hemes and Other Tetrapyrrolesmentioning
confidence: 78%
“…The phototransformable form Pchlide^sinjT has not been detected in roots. The esterified Pchls dominate over the unesterified Pchlide (Me Ewen and Lindsten 1992). PLBs have been reported in plastids of roots (Murakami 1962, Salema !97i, Fadeel and Al-Sani 1972, Oliveira 1982, but some authors question if these structures are identical to PLBs of etiolated leaves (Newcomb 1967, Wbatley 1983).…”
Section: Introductionmentioning
confidence: 99%